Efficacy and safety of tetramethylpyrazine phosphate on pulmonary hypertension: study protocol for a randomized controlled study - Yuqin Chen; Wenjun He; Haiping Ouyang; Chunli Liu; Cheng Hong; Tao Wang; Kai Yang; Wenju Lu; Jian Wang (Trials, 2019)
Abstract Background Tetramethylpyrazine (TMP), an active ingredient in the traditional Chinese herbal medicine Rhizoma Chuanxiong, has been used clinically for the prevention and treatment of cardiovascular disease. The benefits of TMP are largely attributed to its anti-oxidative and vasodilative properties. However, the efficacy of TMP in the treatment of pulmonary hypertension (PH) is unknown. We hypothesized that TMP may have a therapeutic effect in patients with PH. Methods/design A randomized, single-blinded, clinical study with a TMP treatment group and a control group will be conducted to evaluate the efficacy and safety of TMP intervention in patients with PH. The recruitment target is 120 subjects meeting the following criteria: (i) at rest and at sea level, mean pulmonary artery pressure above 20 mmHg and pulmonary capillary wedge pressure below 15 mmHg; (ii) type 1 or 4 PH in the stable phase; (iii) age 15–70 years; (iv) 6-min walk distance between 100 and 450 m; (v) World Health Organization (WHO) functional classification of pulmonary hypertension of II, III, or IV. Subjects will be assigned randomly into two groups at a ratio of 1:2 (control:TMP). Both groups will receive routine treatment, and the treatment group will also receive oral TMP (100 mg) three times a day for 16 weeks. All patients will be followed up for 4, 8, 12, and 16 weeks; symptoms and patient compliance will be recorded. Discussion We aimed to determine the efficacy and safety of TMP for the treatment of PH. Trial registration Chinese Clinical Trial Register, ChiCTR1800018664 . Registered on 2 October 2018.